THE DEVELOPMENT AND STANDARDIZATION OF COVID-19 EXAMINATION LABORATORY: EFFECTIVITY AND CHALLENGES - Siregar, Zulhirdan; Sudirman, Lu; Hutauruk, Rufinus Hotmaulana (Journal of Law and Policy Transformation, 2023)
Thorough COVID-19 pandemic considered done in Indonesia, In terms of surveillance and detection, countermeasures are carried out by examining COVID-19 specimens by the network of COVID-19 examination laboratories. The gold standard for COVID-19 examination is to carry out an RT-PCR (Real Time Polymerase Chain Reaction) test from samples taken with nasopharyngeal and oropharyngeal swabs. Batam City so far has had several laboratories for examining COVID-19 specimens that examined COVID-19 specimens with the RT-PCR test. The number of positive COVID-19 in Batam City until April 18, 2022 was 30,960 people obtained from the results of examinations by the COVID-19 examining laboratory. Arrangements are needed to ensure that all laboratories that carry out testing of COVID-19 specimens have standards and work in maximum capacity so that fast and valid COVID-19 specimen examination results are obtained. This study analyzes the effectiveness of the Decree of the Minister of Health (Kepmenkes) of the Republic of Indonesia Number HK.01.07/MENKES/4642/2021 concerning the Implementation of the Corona Virus Disease 2019 (COVID-19) Examination Laboratory in the development of the COVID-19 examination laboratory in Batam City. Laboratory development is carried out by the Environmental Health and Disease Control Engineering Center (BTKLPP) Class I Batam. This study uses an empirical juridical method with a qualitative approach using secondary data. From the results of the research carried out, it was found that to get fast and valid results, the laboratory for examining COVID-19 specimens must have a standard that is a reference which refers to the Decree of the Minister of Health (Kepmenkes) RI Number HK.01.07/MENKES/4642/2021 concerning Organizing the Corona Virus Disease 2019 (COVID-19) Examination Laboratory and supervisory laboratory in carrying out guidance and supervision of the implementation of the examination of COVID-19 specimens in each of the laboratories for examining COVID-19 specimens in Batam City.